Monthly tax deduction as a final tax: is it a good choice? - Ibrahim, Idawati; Mansor, Muzainah; Saad, Natrah; Bidin, Zainol (International Islamic University Malaysia, 2019)
The case presents the work experience of an employee named Zara. She was a new Chief Financial Officer at a company located in Kuala Lumpur, Malaysia. She was excited and enthusiastic about her new job. However, she became anxious as she was given the responsibility of making a decision regarding a new tax scheme which was recently implemented at her company. Her company wanted her to decide whether to continue with the new tax scheme or revert back to the old tax scheme. She realised that the new tax scheme had both the advantages and disadvantages in its implementation. She had to convince her company with good suggestions if she decided to continue with the new tax scheme.